2012
DOI: 10.1111/bjop.12012
|View full text |Cite
|
Sign up to set email alerts
|

We can work it out: Group decision‐making builds social identity and enhances the cognitive performance of care residents

Abstract: Group-based interventions have been argued to slow the cognitive decline of older people residing in care by building social identification and thereby increasing motivation and engagement. The present study explored the identity-cognition association further by investigating the impact of a group decision-making intervention on cognition. Thirty-six care home residents were assigned to one of three conditions: an Intervention in which they made decisions about lounge refurbishment as a group, a Comparison con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 54 publications
2
40
0
2
Order By: Relevance
“…While all these things are important and may contribute positively to people's positive or negative experiences of different environments, social parameters can also make space functional or dysfunctional (Knight & Haslam, 2010a, b). For example, spaces that allow people to articulate, express, and realize their identities, and which facilitate connections to others with whom they identify, have been found to contribute to individual health and happiness (see also C. Haslam et al, 2014;C. Haslam, Jetten, Haslam, & Knight, 2011).…”
Section: A C C E P T E D Accepted Manuscript Identity and Restorativementioning
confidence: 99%
“…While all these things are important and may contribute positively to people's positive or negative experiences of different environments, social parameters can also make space functional or dysfunctional (Knight & Haslam, 2010a, b). For example, spaces that allow people to articulate, express, and realize their identities, and which facilitate connections to others with whom they identify, have been found to contribute to individual health and happiness (see also C. Haslam et al, 2014;C. Haslam, Jetten, Haslam, & Knight, 2011).…”
Section: A C C E P T E D Accepted Manuscript Identity and Restorativementioning
confidence: 99%
“…In addition, there is a growing evidence that group membership can promote adjustment, coping, and well‐being in vulnerable populations (Jetten et al ., ). This research has found that social identities and group membership can improve well‐being and slow down cognitive decline in older adults (Gleibs et al ., ; Haslam et al ., ), reduce symptoms and recidivism of depression (Cruwys et al ., ; Cruwys, Haslam, Dingle, Jetten et al ., ), and increase well‐being in people with chronic mental health and substance abuse problems (Best et al ., ; Dingle, Brander, Ballantyne, & Baker, ; Dingle, Stark, Cruwys, & Best, ).…”
Section: Introductionmentioning
confidence: 99%
“…In care homes, for example, we have found that when space is managed in ways that accord with, and help to build, residents' sense of shared identity this has substantial positive consequences not only for their comfort but also for their productive use of that space . Building on such observations, a growing number of intervention studies have also shown that distinctly positive consequences for physical, mental, and cognitive health flow from activities that help to build (or reinforce) individuals' sense that they share social identity with other people Haslam et al, 2010;Haslam, Haslam, Knight, et al, 2014;.…”
mentioning
confidence: 99%